A context-centred, root cause analysis of contemporary terrorism. Issue 2 (3rd April 2017) - Sawalha, Ihab Hanna
Abstract : Purpose: The purpose of this paper is threefold: identifying the root causes and other causal factors of terrorism, exploring the recent shifts in terrorist activity, and proposing a context-centred framework for deterring terrorism risk. Design/methodology/approach: The first part of this research is based on extensive up-to-date observations made by the author and extracted from real-life settings and social interactions. The second part is based on a survey questionnaire reflecting public views on terrorism and related issues. Findings: The risk of terrorism risk is increasingly becoming a major concern of all societies including Jordanian. The results have shown that terrorism is context related and that there are several and different root causes for this phenomenon. Many other causal factors have the potential to increase the impact or probability of terrorism risk in Jordan. The existing framework(s) for deterring terrorism risk in Jordan is not adequate and need to be reformed extensively. Practical implications: This study provides insight to the root causes of the potential terrorist activity in Jordan, as well as other causal factors. It is expected to establish a foundation for policy-makers and decision-makers to start considering the causes of social unrest and subsequently develop appropriate frameworks for mitigating terrorism risk. Originality/value: This study is made in a time of unprecedented political instability and terrorist activity in the Middle East and the Arab World. It reflects genuine observations and public opinions, thus providing authentic findings and better understanding of the concerns of the society. Most importantly, the study proposes context-related framework for counteracting terrorism activity and future evolution of this phenomenon in the Middle East, in general, and Jordan, in particular.